Solve the following equation and check your result.

Q.6  8x + 4 = 3 (x – 1) + 7

Answers (1)
D Divya Prakash Singh

We have 

                          8x + 4 = 3 (x - 1) + 7

or                       8x + 4 = 3x - 3 + 7 = 3x + 4

Transposing 3x to the LHS and 4 to the RHS, we get

                         8x - 3x = 4 - 4 = 0

                            5x = 0

Dividing both sides by 5:

                         x = 0 

Check :-   Putting x = 0 in both LHS and RHS:

               LHS :- 8x + 4 = 8(0) + 4 = 4

               RHS :- 3(x-1) + 7 = 3(-1) + 7 = -3 + 7 = 4

Hence,                LHS = RHS 

Exams
Articles
Questions